Institutional Flows of Communication for Young People on Instagram and the Use of Visual Images - Leone, Stefania; Della Mura, Miriam (PARTECIPAZIONE E CONFLITTO, 2020)
Public communication in digital space is entering a phase of profound change due to the redefinition of the forms of production, dissemination and use of content in institutional networks. This article contributes to research carried out on public communication news flows of SNSs, presenting an analysis focusing on the visual content posted on institutional information channels dedicated to young people and managed by youth policy actors. The content of photos was analyzed in relation to 6 categories of public communication topics, 3 categories of communication aims, 6 categories of visual elements and 10 thematic areas. The empirical basis consists of 702 images taken from 15 accounts of Italian and European youth policy Instagram channels. The results show the main features of institutional flows on Instagram and a comparison with what has emerged from previous research projects relating to Facebook and Twitter. The findings focus on institutional topics and promotional aims and on the weaknesses of the flow of images in terms of social and political issues, engagement, public-service information, semantic autonomy and emotional impact. The limits that emerge from the research identify certain critical questions which indicate a need for further investigation with respect to relationships occurring between public news flows, young people, information requirements and social networks in the public sphere.